Environmental management in the area of the Callao concentrate tanks - Iglesias, Silvia (2008)
The objective of this article is to present the results of the research study carried out at the Research Institute of the Faculty of Geological, Mining, Metallurgical and Geographical Engineering of the Universidad Nacional Mayor de San Marcos in 2004 and compare them with the data. from 2004 to 2007 provided by Cormín Callao - Depósito de Concentrados. The comparison is made in order to determine if the environmental management actions incorporated in the years 2005, 2006 and 2007 are giving results. The data that is compared corresponds to the main indicator such as the particulate material less than 10 microns: PM10. It is proposed to update the environmental management with the consequent improvement in the quality of life in the area around the Callao concentrate tanks, establishing adequate environmental management that includes corrective actions defined based on the situational analysis and incorporating useful environmental information.